Pancasila: Cinta Kasih Yang Mempersatukan - Moses William Yuwono (FOCUS, 2020)
Recent cases of discrimination and intolerance have threatened the unity of Indonesia. We may forget that the unity in diversity (Bhineka Tunggal Ika) is a ‘given’ thing for the inhabitants of Indonesia. This article is a descriptive-critical reflection to this given-unity-in-diversity in the light of Pancasila as the practical-philosophy of Indonesian people. In the face of Indonesian people’s ethnicity, race, and religion diversities, a unifying love is needed, which is none other than the Pancasila itself.